Antioxidant capacity and sensory quality of soy-based powder drink mix enriched with functional hydrolysates of swiftlet (Aerodramus fuciphagus) - Hazimah Mohd Aris; Zalifah Mohd Kasim; Saiful Irwan Zubairi; Abdul Salam Babji (Arabian Journal of Chemistry, 2023)
The enrichment with low amount of bioactive protein of spray-dried edible bird’s nest hydrolysates (EBNH) (3.0 %) in view of its cost and high solubility provided significant value added to the overall in vitro antioxidant capacity of soy-based powder drink mix (PDM). Its beverage (12.5 % concentration, consistency index 0.39 Pa.sn) antioxidant capacity as measured by ABTS and FRAP was comparable (p > 0.05) but significantly higher than antioxidant assays of FCR and DPPH. The respective antioxidant capacity of the PDM beverage in terms of trolox equivalent (TE) and gallic acid equivalent (GAE) were 21.95 TE mg/g, 20.75 TE mg/g, 2.93 TE mg/g and 14.72 GAE mg/g for FRAP, ABTS, DPPH and FCR. Depending on antioxidant assay, EBNH in beverage of PDM contributed an increase in the range of 3.7–9.3 % (which was significant (p < 0.05) according to ABTS and FCR assays) or about 6.0 % to its overall antioxidant capacity. The interaction among the antioxidant activity of all the food product’s ingredients is antagonistic since the difference between the expected and observed total antioxidant potential is significantly higher (p < 0.05) for all antioxidants assays, except FCR. The beverage of PDM has excellent sensory quality. It is sugar free and high protein PDM that has excellent cocoa flavour and possesses sufficient sweetness with acceptable beany aroma and taste when served as hot beverage.